Peranan Guru dalam Mengonstruksi Karakter Islami Siswa Melalui Metode Pembelajaran Berbasis Masalah di Madrasah Aliyah Negeri Majene - Indah Rahayu (Journal on Education, 2023)
This study examines the teacher's role in constructing students' Islamic character through the problem-based learning method, which is a type and method of classroom management needed to support the student character approach in teaching and learning. This method is explored by thinking critically, independently and inclusively, to address the challenges of teachers and students in teaching and learning in the technological era towards 5.0. As someone who has complex knowledge, the role of the teacher greatly influences students' character regarding a critical-inclusive attitude on the one hand and an independent attitude on the other. In responding to challenges that are not easy, at least teachers must prepare learning methods that are appropriate to the current generation, in order to maintain the existence of teachers which will certainly have an impact on their students. In this regard, problem-based learning methods are very effectively implemented by teachers in schools to adapt students' characters to be in line with the demands of the times by referring to conventional learning models or methods without marginalizing the daily patterns of teachers and students.